Choosing an appropriate size valve for transcatheter pulmonary valve implantation in a native right ventricle outflow tract - Muthukumaran C Sivaprakasam; J Raja Vijendra Reddy; Rajaguru Ganesan; Anuradha Sridhar; Neville Solomon; Musth Janeel Moosa; Zeeshan Sakina Lakhani; Sengottuvelu Gunasekaran (Wolters Kluwer Medknow Publications, 2022)
Introduction: Transcatheter pulmonary valve implantation has been an effective treatment for dysfuntional right ventricular tract outflow tract (RVOT). Defining a landing zone before the intervention is crucial in patients with native RVOT. Improper sizing and undefined landing zone will lead to embolization. Methods: It is a retrospective observational study from August 2020 to December 2020 in native RVOT. Three patients who had significant Right ventricle dilatation were analyzed. The multi-slice computed tomography (MSCT) with magnetic resonance imaging and angiography data of all patients before the procedure were analyzed. All patients underwent an angiogram in the same sitting, before the procedure to assess the landing zone, valve diameter as well as the risk for coronary compression. We chose a valve based on valve area 23%-25% more than the area at the waist during balloon sizing. Results: All three patients underwent successful valve implantation. Valve sizes used were 27.5 mm in one and 32 mm in the other two. The mean RVOT gradient postprocedure was 11.5 mm Hg and pre procedure was 43 mmHg. There were no complications during the procedure or at a mean follow-up of 3.6 months. Conclusion: The balloon sizing gives the true narrowest diameter in comparison with MSCT, and increasing this area by 23%-25% will give the appropriate valve size for successful implantation.